Leadership style head of polytechnic department and regard with to work culture - Zakaria, Normah; Jamaludin, Nur Hasliza; Naim, Nor Azlin; Nur Azzarina, Khamis (International Knowledge Sharing Platform, 2015)
This study aims to look at the leadership style of the heads of departments in technical education and its relationship to the work culture among lecturers Polytechnic Sultan Abdul Halim Mu'adzam Shah in Jitra, Kedah. This research is very important to the head of polytechnic and lecture to work in the good condition with the good leadership. This study specifically for identifying leadership style of department heads and identifying cultural favourite work by guest lecturers by lecturers own. In addition, this study also aims to identify whether there is a significant relationship between leadership style and work culture based on the view lecturers in polytechnics. This study used a survey method through questionnaires investigator. Measuring tool -LEADER Behaviour Description Questionnaireǁ (LBDQ) used to measure the leadership style of the heads of departments and task-oriented dimension oriented human relations. Measuring tools work culture lecturers used to measure the kind of work culture in polytechnics favoured by both the dimensions of leadership style. Respondents were lecturer’s population a total of 290 people in four departments in polytechnic master. Data processing involves statistics a descriptive measurement frequency, mean, standard deviation and also percentage. Data processed using inferential statistics, including Pearson correlation coefficient, ANOVA and t-Test. The study found that leadership style department heads on evaluation lecturers are high on both dimensions of the oriented dimension task-oriented and dimension of human relationships. But leadership style human relations-oriented leadership style is the key department heads polytechnics. The study also found that corporate culture is a culture of bureaucratic work favoured by lecturers in polytechnics.